2004
DOI: 10.1016/j.febslet.2004.07.077
|View full text |Cite
|
Sign up to set email alerts
|

Stimulators of AMP‐activated protein kinase inhibit the respiratory burst in human neutrophils

Abstract: In the present study, we have examined the potential ability of 5 0 -AMP-activated protein kinase (AMPK) to modulate NADPH oxidase activity in human neutrophils. AMPK activated with either 5 0 -aminoimidazole-4-carboxamide ribonucleoside (AICAR) or with 5 0 -AMP significantly attenuated both phorbol 12-myristate 13-acetate (PMA) and formyl methionyl leucyl phenylalanine-stimulated superoxide anion ðO À 2 Þ release by human neutrophils, consistently with a reduced translocation to the cell membrane and phosphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 48 publications
(56 reference statements)
6
59
1
Order By: Relevance
“…This is supported by data showing that the activation of adenosine monophosphate kinases in a state of low cellular energy contributes to a reduction in host defense mechanisms. 30 The clinical importance of these neutrophil abnormalities, which are identified by a high resting oxidative burst greater than or equal to 55% and a reduced phagocytic capacity (relative GMFI Ͻ 42%), are highlighted by the observation of increased risk of infection and the association with organ failure and mortality in these patients. It is notable that this group of patients in our study had infections with multiple organisms despite antibiotic therapy within a relatively short time frame.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by data showing that the activation of adenosine monophosphate kinases in a state of low cellular energy contributes to a reduction in host defense mechanisms. 30 The clinical importance of these neutrophil abnormalities, which are identified by a high resting oxidative burst greater than or equal to 55% and a reduced phagocytic capacity (relative GMFI Ͻ 42%), are highlighted by the observation of increased risk of infection and the association with organ failure and mortality in these patients. It is notable that this group of patients in our study had infections with multiple organisms despite antibiotic therapy within a relatively short time frame.…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggest the following: 1) that an increase in endogenous FFA availability augments ROS generation, and 2) that AMPK activation during lipolysis probably limits this oxidative stress. Studies in which AMPK activity in the adipocyte is down-regulated by genetic means are needed to confirm this conclusion; however, it is noteworthy that a similar effect of AMPK activation on ROS generation has been observed in human endothelial cells incubated with linoleate or palmitate (10,46) and in neutrophils treated with phorbol myristate acetate (12). In both situations, AMPK activation was shown to diminish NAD(P)H oxidase activity.…”
Section: Discussionmentioning
confidence: 91%
“…In clinical studies, ETC-1002 has not only demonstrated improved lipid profi les but also revealed signifi cantly attenuated levels of hsCRP ( 19 ), an independent risk factor for CAD and a well-established clinical biomarker of infl ammation ( 20,21 ). Pharmacological activation of AMPK has been previously shown to limit infl ammatory response in vitro and in vivo (22)(23)(24)(25)(26), and several signaling pathways, including Akt, GSK, SIRT, and NFkB, have been associated with anti-infl ammatory consequences of AMPK activation ( 17,(27)(28)(29). While the exact mechanism of AMPK-dependent regulation of the immune response remains unclear, inhibition of mitogen-activated protein kinases (MAPK), such as JNK and p38, has been recently linked to AMPK-dependent anti-infl ammatory signaling ( 30 ).…”
Section: Protein Arraysmentioning
confidence: 99%